Wpływ systemów zarządzania jakością na spełnienie oczekiwań klientów oraz wzrost jakości produktów w wybranych przedsiębiorstwach mleczarskich na obszarze nazywanym zielonymi płucami Polski - Wysokińska, Aneta (Influence a Quality Management System on the Customer Satisfaction and High Quality of Products in the Selected Diary Company, 2005)
Success of an organization can result from implementing and maintaining a management system that is designed to constantly improve performance while addressing the needs of all interested parties.As one of the performance of quality management system, the organization shall monitor information relating to customer perception as to whether the organization has met customer requirements.High quality of products is an important element of being competitive on the market. Quality management systems can assist organizations in enhancing customer satisfaction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 429-433